THE PAIN OF A SPOT ON THE FOREHEAD (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the story “Dog‘” by the writer Khaliyor Safarov. Some symbolic details in it are commented on, as well as a comparative analysis of image and dialogue motives with other works.